Annotated bibliography of bibliographies on selected government publications and supplementary guides to the Superintendent of Documents classification system. - Body, Alexander C.; Kovács, Gábor (Choreographer) (Western Michigan University, 1968)
1967- on microfiche in pocket at back of 5th-11th supplement.